Antimicrobial Resistance Trends of Escherichia coli Isolates: A Three-Year Prospective Study of Poultry Production in Spain - Sandra Sevilla-Navarro; Pablo Catalá-Gregori; Jan Torres-Boncompte; Maria Teresa Orenga; Josep Garcia-Llorens; Verónica Cortés (Antibiotics, 2022)
Antimicrobial resistance (AMR) poses a major threat to health worldwide. Poultry products are one of the main threats, due to the transmission of antimicrobial resistance genes throughout the food chain. Escherichia coli is the main cause of mortality in the poultry industry, mainly mitigated with antibiotics, but due to the high genetic strain variability, recurrent outbreaks of multidrug resistant E. coli take place. The major challenge to tackling AMR is understanding the burden of resistance. For this reason, one of the main strategies is monitoring AMR by phenotypic characterisation. Our study aimed to monitor the resistance of E. coli strains isolated from the poultry sector over a period of three years (2019–2021) to provide information on the resistance magnitude and trends. Promising results have been found concerning the low frequency of resistance to cephalosporins, polymyxin, and fluoroquinolones. However, levels of resistance found to antimicrobials such as erythromycin (100%), tylosin (98%), or penicillin (97%) suggest the need to continue working on the limitation of use of antimicrobials in poultry to achieve the demise of MDR.